Kacang Nanny / Mohd Izzat Syazwan Che Amran - Che Amran, Mohd Izzat Syazwan (2021)
Kacang Nanny provides food to ensure that every customer is satisfied. This identifies those who want to nibble on nuts. It is a reasonably priced product. This product is also marketed to children, families, and students. The Kacang Nanny marketing approach emphasizes on quality and pricing. It provides a reasonable price because many people desire to purchase this goods, particularly in Kedah. As a result, I devised a marketing plan that entices people to purchase Kacang Nanny. The flavor is delectable and the product is of good quality. Siti Zambea Binti Abu Bakar @ Awang is in charge of Kacang Nanny. I created Facebook in order to grow my business through social media and I learned how to post Facebook posts for commercial products such as teaser posts, soft sells, and hard sells. I need to promote the product on social media throughout Malaysia, particularly in Kedah. It also learns how to use the eUsahawan Portal to record sales via the eUsahawan Portal. Selling this product as my personal initiative is a challenge for me.